The Relationship Between Parental Care and Pain in Children With Headache: A Narrative Review. Issue 6 (31st May 2020) - Natalucci, Giulia; Faedda, Noemi; Baglioni, Valentina; Guidetti, Vincenzo
Abstract : Purpose: In migraine or primary headache in children, parents play a fundamental role in pain management. For this narrative review, PubMed, Google Scholar, and Psych Info were searched using the terms "parent headache", "mother/father headache", "parental impact headache", "alexithymia parents headache", "catastrophizing parent headache", "family headache", "children parent headache", and "quality of life family headache". Articles were chosen for inclusion based on their relevance in to the topic. Overview: Several parental and psychological characteristics can influence in children and adolescent headache, such as parental attitudes as oppressive or overprotective; punitive parenting styles; familial psychological symptoms, especially anxiety and depression; catastrophizing about their child's pain or excessive worry about their child's headache; inability to express emotions; and feelings that may lead to somatization problems. Discussion: Parents' attitudes and behaviors toward their child's headache have a strong relation with the severity of headache attacks. Mothers seem to have more influence than fathers on children's pain and emotional regulation. We suggest that the presence of caregiver‐child transmission of maladaptive coping strategies, arising from difficulties expressing emotion, may lead to incorrect management of headache pain, further facilitating headache chronification.